UV Light‐Emitting Diodes: Enhancement of Heat Dissipation in Ultraviolet Light‐Emitting Diodes by a Vertically Oriented Graphene Nanowall Buffer Layer (Adv. Mater. 29/2019). Issue 29 (16th July 2019) - Ci, Haina; Chang, Hongliang; Wang, Ruoyu; Wei, Tongbo; Wang, Yunyu; Chen, Zhaolong; Sun, Yuanwei; Dou, Zhipeng; Liu, Zhiqiang; Li, Jinmin; Gao, Peng; Liu, Zhongfan
Abstract : The use of vertically oriented graphene nanowalls as a buffer layer for the growth of high‐quality AlN film on a sapphire substrate to improve heat dissipation is proposed by Tongbo Wei, Zhiqiang Liu, Peng Gao, Zhongfan Liu, and co‐workers in article number 1901624 . Thus, their as‐fabricated light‐emitting diode shows a 37% increasement of light output power under a high injection current (350 mA) due to the temperature reduction and strain relaxation.